Zeitstrukturen und Verkehr: Individualisierung der Mobilität? Tagesganglinien des Verkehrs 1976 bis 2002. - Scheiner, Joachim (Deutscher Verkehrs-Verl., 2006)
In der Mobilitätsforschung gibt es eine bisher unbelegte These über die Auswirkungen der Individualisierung der Gesellschaft im historischen Verlauf auf die zeitliche Verteilung von Wegemustern. Der Beitrag untersucht anhand der KONTIV-Wellen 1976, 1982, 1989 und 2002, inwieweit sich die These einer zunehmenden Individualisierung des Verkehrsverhaltens im Sinne einer Nivellierung ehemals charakteristischer tages- und wochenzeitlicher Wegeverteilungen für die vergangenen Jahrzehnte stützen lässt. difu

Based on the KONTIV surveys 1976, 1982, 1989 and 2002, the paper investigates as to whether there is evidence for the hypothesis of increasing individualisation of travel behaviour, in terms of a more even daily and weekly distribution of trips. The results indicate that the distribution of job trips, maintenance trips and trips in general over the day has become distinctly more even. What is more, trip distributions have been shifted in time. The changes might be interpreted with regard to demographic change, structural change of economy and flexibilisation of working hours and business hours, and, possibly, structural changes in leisure time. However, there are methodological effects as well, resulting from differences between the four KONTIV surveys. This is particularly true for the investigation of weekly trip distributions. difu
Keywords: Verkehr; Verkehrsstatistik; Empirische Sozialwissenschaft; Verkehrsmittelwahl; Verkehrsverhalten; Mobilität; Verkehrsplanung; Verkehrsnachfrage; Zeit; Erhebung; Zielverkehr; Lebenssituation; Arbeitsweg; Tageszeit; Zeitstruktur